P-Toluenesulfonic acid-promoted autocatalytic hydrolyzation of 1-tosyl-1, 2, 3-triazoles. Issue 10 (19th May 2018) - Dong, Haohao; Zhang, Dongdong; Fang, Renjie; Du, Qingyang; Dong, Zhuoya; Wei, Hao; Shi, Min; Wang, Feijun
ABSTRACT: The first example of autocatalytic hydrolyzation of 4-aryl-1-tosyl-1, 2, 3-triazoles induced by p -toluenesulfonic acid was reported, providing an effective and metal-free synthetic approach to deliver a broad range of new 4-aryl-2 H -1, 2, 3-triazoles in good yields. The kinetic profile of this hydrolyzation suggested that this reaction has exponential autocatalytic behavior. GRAPHICAL ABSTRACT: